Use of radionuclide imaging to determine gastric emptying of carbohydrate solutions during exercise. Issue 1 (March 1996) - MacLaren, D; Miles, A; O'Neill, I; Critchley, M; Grime, S; Stockdale, H
Abstract : OBJECTIVE--To investigate the repeatability of continual assessment of the gastric emptying rates of carbohydrate solutions in exercising subjects using 99mtechnetium labelling. METHODS--Gastric emptying of a 5% glucose solution and an iso-osmotic maltodextrin solution was measured using 3 MBq of 99mtechnetium labelled diethylene triamine penta-acetic acid (DTPA) and continuous gamma camera imaging in five male subjects. The subjects performed four 1 h trials at 70% VO2 peak on a cycle ergometer. After 15 min, 200 ml of a radiolabelled solution of glucose or maltodextrin were ingested in a blind crossover protocol. The two solutions were each ingested on separate occasions (trial 1 and trial 2) to establish repeatability. RESULTS--Statistical analysis showed no differences between trial 1 and trial 2 for both solutions. There were no significant differences for the emptying rates between the two test solutions. CONCLUSIONS--Posterior imaging using a computer linked gamma camera following the ingestion of 99mtechnetium labelled DTPA mixed with carbohydrate solutions provides a repeatable method of assessing gastric emptying characteristics in exercising subjects. This technique showed no significant differences between the emptying rates of a single dose of iso-osmotic glucose or maltodextrin solution.